Pengelompokan Daerah Produksi Tanaman Biofarmaka Menurut Jenis Tanaman dengan Metode K – Means Clustering - Kholifah, Fitri Nur; Bahri, Saiful (ESTIMASI: Journal of Statistics and Its Application, 2025)
Biopharmaceutical plants or commonly called medicinal plants are plants in which one, several or all parts of these plants contain substances or active ingredients that are useful for body health, disease healing or cosmetic ingredients. Based on data from the Central Bureau of Statistics (BPS), the production of biopharmaceutical plants varies in each region. So that in an effort to equalize the results of biopharmaceutical production in Indonesia, it is necessary to group areas that have the potential to produce biopharmaceutical plants to find out which areas produce in large or small quantities. In this research, a method is needed to facilitate the grouping of biopharmaceutical producing regions, one of which is the clustering analysis method. . One of the methods that can be used in cluster analysis is the k-means clustering algorithm. The results of this study indicate that there are 5 provinces that are included in cluster 1 (C1) with the category of low biopharmaceutical production in 2021. Meanwhile, 29 other provinces are included in the cluster. 2 (C2) with the category of high biopharmaceutical production areas in 2021.